Perancangan Interior Pusat Informasi dan Pengembangan Penyandang Intellectual – Learning Disability di Surabaya - Lyvia Tjiasmanto; Purnama Esa Dora Tedjokoesoemo; Anik Rakhmawati (Intra, 2019)
People’s awareness of Intellectual Learning disability, a disability that affects child’s cognitive and learning ability is poor. Hence a child’s cognitive and learning ability is an important factor for their upcoming developmental phase. The purpose of the design is to give information and facility in both cognitive and psychology to patient, patient’s family and also society. Design method using 4 methods from Bryan Lawson that consists four stages which are Assimilation, General study, Development and Communication. The result of the design is an Information and Developmental Center with the concept “Breathe” that uses nature element in approach, presenting information with innovative and creative, also refreshing colors to present relaxing and comforting ambience to facilitate the activities inside.